2003
DOI: 10.1002/pmic.200300401
|View full text |Cite
|
Sign up to set email alerts
|

Detection of protein‐protein interactions and a group of immunoglobulin G‐associated minor proteins in human plasma by nondenaturing and denaturing two‐dimensional gel electrophoresis

Abstract: The dissociation of noncovalently associated protein-protein complexes in human plasma was examined by comparing two-dimensional gel electrophoresis (2-DE) patterns obtained in two different electrophoretic conditions. A type I 2-DE pattern was obtained running nondenaturing isoelectric focusing (IEF) followed by nondenaturing gel electrophoresis and a type II 2-DE pattern was nondenaturing IEF followed by sodium dodecyl sulfate gel electrophoresis. Micro-sized gels (internal diameter(id) 1.3 x 35 mm polyacryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…1B, which were obvious only after silver staining, would not be suited for the analysis. Previously, we have reported that the minor proteins are likely to form high-molecular-mass proteins under non-denaturing conditions and they are present in 0-4% PEG fractions or in 0-35% AS fractions 1) . Then we employed AS fractionation to enrich them and the 0-35% AS fraction (described in Section 2.2, ca.…”
Section: Type-ii 2-de Of 0-35% As Fraction and Maldi-tof Ms-pmf Analymentioning
confidence: 99%
See 2 more Smart Citations
“…1B, which were obvious only after silver staining, would not be suited for the analysis. Previously, we have reported that the minor proteins are likely to form high-molecular-mass proteins under non-denaturing conditions and they are present in 0-4% PEG fractions or in 0-35% AS fractions 1) . Then we employed AS fractionation to enrich them and the 0-35% AS fraction (described in Section 2.2, ca.…”
Section: Type-ii 2-de Of 0-35% As Fraction and Maldi-tof Ms-pmf Analymentioning
confidence: 99%
“…When IEF was run with electrode solutions kept around 30°C and the 2-DE gel was stained with CBB, human plasma proteins were separated as shown in Figure 1A. The minor spots which had been detected at pI 5.5-7.5 and mass 8-45 kDa 1) are not obvious in the 2-DE pattern, but when the gel was further stained with silver ( Fig. 1B), more than 50 spots were detected in the corresponding region.…”
Section: Maldi-tof Ms Of Tryptic Peptides and Peptide Mass Fingerprinmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lower resolution and narrower separation of basic proteins or complexes are major limitations of CNE compared with BNE or hrCNE (13). Nondenaturing micro-two dimensional electrophoresis (micro 2-DE) was developed later to overcome the lower resolution of CNE (14). Although it has been used widely in plasma and cytoplasm protein complex investigations (15)(16)(17), it is still not suitable for basic protein analysis with a pI above the pH of the gel.…”
mentioning
confidence: 99%
“…The samples after different duration of alkaline treatment, but containing the same quantity of a protein (1.0 mg), were subjected to SDS-PAGE employing micro slab gels (38 mm638 mm61 mm, 8.4%-17.85% T and 5% C polyacrylamide gradient gel), then the gels were stained with CBB R-250 and destained [13]. Quantitation of the stained protein bands on the gel was performed using a scanner and an image analysis software (Phoretics 2-D Full; Nonlinear Dynamics, Newcastle, UK) [14]. …”
mentioning
confidence: 99%